THE FULFILLMENT OF WOMEN'S PRISONERS' RIGHTS AS ONE OF THE VULNERABLE GROUPS IN CORRECTIONAL INSTITUTIONS - Subroto, Mitro; Siahaan, Argendo (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article discusses the fulfillment of women's prisoners' rights in correctional institutions (Lapas) in Indonesia through a literature review approach. The main focus is on the challenges faced by female inmates, including gender inequality, limited facilities, and specific health issues. Additionally, the article evaluates existing policies and programs, such as the ratification of international conventions and related legislation, as well as efforts to fulfill the specific rights of women in correctional facilities. The findings indicate that although there are some policies in place, their implementation still faces significant obstacles. The article recommends the need for policy reforms, improved facilities, and specialized training for staff to more effectively and fairly meet the rights of female inmates. Keywords: Rights; Inequality; Gender; Policy